THE EFFECTS OF ONLINE LEARNING ON STUDENTS SPEAKING SKILL ACHIEVEMENT - Suci Dhea Anjani; Kelik Wachyudi (IKIP Siliwangi, 2022)
This research expects to untangle online learning outcomes on students' speaking skill achievement during the pandemic. The method employed in this research was secondary data collection because it was reasonable in this present situation and as an effort to diminish the spread of COVID-19. The number of subjects of the research was seven articles that analyzed secondary students. The research provides information related to the students' speaking skills achievement through online learning. This study reveals that most students decrease learning speaking skills through online learning mode during pandemic COVID-19. The researchers discovered a few problems during the learning process, such as; decreasing pronunciation, lack of seriousness, and becoming less enthusiastic about learning to speak English. Keywords: Online Learning, Speaking Skills, Achievement